Advances in remote sensing of emperor penguins: first multi-year time series documenting trends in the global population - LaRue, Michelle; Iles, David; Labrousse, Sara; Fretwell, Peter; Ortega, David; Devane, Eileen; Horstmann, Isabella; Viollat, Lise; Foster-Dyer, Rose; Le Bohec, Céline; Zitterbart, Daniel; Houstin, Aymeric; et al. (Proceedings of the Royal Society of London, Series B: Biological Sciences, 2024)
Like many polar animals, emperor penguin populations are challenging to monitor because of the species’ life history and remoteness. Consequently, it has been difficult to establish its global status, a subject important to resolve as polar environments change. To advance our understanding of emperor penguins, we combined remote sensing, validation surveys and using Bayesian modelling, we estimated a comprehensive population trajectory over a recent 10-year period, encompassing the entirety of the species’ range. Reported as indices of abundance, our study indicates with 81% probability that there were fewer adult emperor penguins in 2018 than in 2009, with a posterior median decrease of 9.6% (95% credible interval (CI) −26.4% to +9.4%). The global population trend was −1.3% per year over this period (95% CI = −3.3% to +1.0%) and declines probably occurred in four of eight fast ice regions, irrespective of habitat conditions. Thus far, explanations have yet to be identified regarding trends, especially as we observed an apparent population uptick toward the end of time series. Our work potentially establishes a framework for monitoring other Antarctic coastal species detectable by satellite, while promoting a need for research to better understand factors driving biotic changes in the Southern Ocean ecosystem.
CRIS-Team Scopus Importer:2024-03-22
Keywords: Antarctica; Aptenodytes forsteri; Bayesian modelling; high-resolution satellite imagery; Southern Ocean

A low-cost uniaxial cell stretcher for six parallel wells - Kah, Delf-Thorge Eric; Winterl, Alexander; Přechová, Magdalena; Schöler, Ulrike; Schneider, Werner; Friedrich, Oliver; Gregor, Martin; Fabry, Ben (HardwareX, 2021)
Cells in the lungs, the heart, and numerous other organs, are constantly exposed to dynamic forces and deformations. To mimic these dynamic mechanical loading conditions and to study the resulting cellular responses such as morphological changes or the activation of biochemical signaling pathways, cells are typically seeded on flexible 2D substrates that are uniaxially or biaxially stretched. Here, we present an open-source cell stretcher built from parts of an Anet A8 3D printer. The cell stretcher is controlled by a fully programmable open-source software using GCode and Python. Up to six flexible optically clear substrates can be stretched simultaneously, allowing for comparative multi-batch biological studies including microscopic image analysis. The cell yield from the cell culture area of 4 cm2 per substrate is sufficient for Western-blot protein analysis. As a proof-of-concept, we study the activation of the Yes-associated protein (YAP) mechanotransduction pathway in response to increased cytoskeletal tension induced by uniaxial stretching of epithelial cells. Our data support the previously observed activation of the YAP transcription pathway by stretch-induced increase in cytoskeletal tension and demonstrate the suitability of the cell stretcher to study complex mechano-biological processes.
CRIS-Team Scopus Importer:2021-01-01
Keywords: 3D printer; Cell Mechanics; Cell stretcher; Mechanosensing; Uniaxial stretch; YAP

Biologging of emperor penguins-Attachment techniques and associated deployment performance - Houstin, Aymeric; Paranhos Zitterbart, Daniel; Winterl, Alexander; Richter, Sebastian; Planas-Bielsa, Víctor; Chevallier, Damien; Ancel, André; Fournier, Jérôme; Fabry, Ben; Le Bohec, Céline (PLoS ONE, 2022)
An increasing number of marine animals are equipped with biologgers, to study their physiology, behaviour and ecology, often for conservation purposes. To minimise the impacts of biologgers on the animals' welfare, the Refinement principle from the Three Rs framework (Replacement, Reduction, Refinement) urges to continuously test and evaluate new and updated biologging protocols. Here, we propose alternative and promising techniques for emperor penguin (Aptenodytes forsteri) capture and on-site logger deployment that aim to mitigate the potential negative impacts of logger deployment on these birds. We equipped adult emperor penguins for short-term (GPS, Time-Depth Recorder (TDR)) and long-term (i.e. planned for one year) deployments (ARGOS platforms, TDR), as well as juvenile emperor penguins for long-term deployments (ARGOS platforms) in the Weddell Sea area where they had not yet been studied. We describe and qualitatively evaluate our protocols for the attachment of biologgers on-site at the colony, the capture of the animals and the recovery of the devices after deployment. We report unprecedented recaptures of long-term equipped adult emperor penguins (50% of equipped individuals recaptured after 290 days). Our data demonstrate that the traditional technique of long-term attachment by gluing the biologgers directly to the back feathers causes excessive feather breakage and the loss of the devices after a few months. We therefore propose an alternative method of attachment for back-mounted devices. This technique led to successful year-round deployments on 37.5% of the equipped juveniles. Finally, we also disclose the first deployments of leg-bracelet mounted TDRs on emperor penguins. Our findings highlight the importance of monitoring potential impacts of biologger deployments on the animals and the need to continue to improve methods to minimize disturbance and enhance performance and results.
CRIS-Team Scopus Importer:2022-08-12

CameraTransform: A Python package for perspective corrections and image mapping - Gerum, Richard; Richter, Sebastian; Winterl, Alexander; Mark, Christoph; Fabry, Ben; Le Bohec, Céline; Paranhos Zitterbart, Daniel (SoftwareX, 2019)
Camera images and video recordings are simple and non-invasive tools to investigate animals in their natural habitat. Quantitative evaluations, however, often require an exact reconstruction of object positions, sizes, and distances in the image. Here, we provide an open source software package to perform such calculations. Our approach allows the user to correct for perspective distortion, transform images to “bird's-eye” view projections, or transform image-coordinates to real-world coordinates and vice versa. The extrinsic camera parameters that are necessary to perform such image corrections and transformations (elevation, tilt/roll angle, and heading of the camera) are obtained from the image using contextual information such as a visible horizon, GPS coordinates of landmarks, known object sizes, or images of the same object obtained from different viewing angles. All mathematical operations are implemented in the Python package CameraTransform. The performance of the implementation is evaluated using computer-generated synthetic images with known camera parameters. Moreover, we test our algorithm on images of emperor penguin colonies, and demonstrate that the camera tilt and roll angles can be estimated with an error of less than one degree, and the camera elevation with an error of less than 5%. The CameraTransform software package simplifies camera matrix-based image transformations and the extraction of quantitative image information. An extensive documentation and usage examples in an ecological context are provided at http://cameratransform.readthedocs.io.
CRIS-Team Scopus Importer:2019-10-08
Keywords: Camera lens distortions; Geo-referencing; Perspective projection; Quantitative image analysis

CameraTransform: a Scientific Python Package for Perspective Camera Corrections - Gerum, Richard; Richter, Sebastian; Winterl, Alexander; Fabry, Ben; Paranhos Zitterbart, Daniel (arXiv, 2017)

Cryopreservation impairs 3-D migration and cytotoxicity of natural killer cells - Mark, Christoph; Czerwinski, Tina; Roessner, Susanne; Mainka, Astrid; Hörsch, Franziska; Heublein, Lucas; Winterl, Alexander; Sanokowski, Sebastian; Richter, Sebastian; Bauer, Nina; Angelini, Thomas E.; Schuler, Gerold; et al. (Nature Communications, 2020)
Natural killer (NK) cells are important effector cells in the immune response to cancer. Clinical trials on adoptively transferred NK cells in patients with solid tumors, however, have thus far been unsuccessful. As NK cells need to pass stringent safety evaluation tests before clinical use, the cells are cryopreserved to bridge the necessary evaluation time. Standard degranulation and chromium release cytotoxicity assays confirm the ability of cryopreserved NK cells to kill target cells. Here, we report that tumor cells embedded in a 3-dimensional collagen gel, however, are killed by cryopreserved NK cells at a 5.6-fold lower rate compared to fresh NK cells. This difference is mainly caused by a 6-fold decrease in the fraction of motile NK cells after cryopreservation. These findings may explain the persistent failure of NK cell therapy in patients with solid tumors and highlight the crucial role of a 3-D environment for testing NK cell function.
CRIS-Team Scopus Importer:2020-10-23

Cryopreservation reduces the Ability to migrate and the Cytotoxicity of natural Killer Cells in 3D: Possible Effects on cellular Immunotherapy - Mark, Christoph; Czerwinksi, T.; Roessner, S.; Mainka, Astrid; Hoersch, F.; Heublein, L.; Winterl, Alexander; Sanokowski, Sebastian; Richter, S.; Bauer, N.; Angelini, T.; Schuler, Gerold; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11

Detecting long-range interactions between migrating cells - Metzner, C.; Hörsch, F.; Mark, Christoph; Czerwinski, Tina; Winterl, Alexander; Voskens, Caroline; Fabry, Ben (Scientific Reports, 2021)
Chemotaxis enables cells to systematically approach distant targets that emit a diffusible guiding substance. However, the visual observation of an encounter between a cell and a target does not necessarily indicate the presence of a chemotactic approach mechanism, as even a blindly migrating cell can come across a target by chance. To distinguish between the chemotactic approach and blind migration, we present an objective method that is based on the analysis of time-lapse recorded cell migration trajectories: For each movement step of a cell relative to the position of a potential target, we compute a p value that quantifies the likelihood of the movement direction under the null-hypothesis of blind migration. The resulting distribution of p values, pooled over all recorded cell trajectories, is then compared to an ensemble of reference distributions in which the positions of targets are randomized. First, we validate our method with simulated data, demonstrating that it reliably detects the presence or absence of remote cell-cell interactions. In a second step, we apply the method to data from three-dimensional collagen gels, interspersed with highly migratory natural killer (NK) cells that were derived from two different human donors. We find for one of the donors an attractive interaction between the NK cells, pointing to a cooperative behavior of these immune cells. When adding nearly stationary K562 tumor cells to the system, we find a repulsive interaction between K562 and NK cells for one of the donors. By contrast, we find attractive interactions between NK cells and an IL-15-secreting variant of K562 tumor cells. We therefore speculate that NK cells find wild-type tumor cells only by chance, but are programmed to leave a target quickly after a close encounter. We provide a freely available Python implementation of our p value method that can serve as a general tool for detecting long-range interactions in collective systems of self-driven agents.
CRIS-Team Scopus Importer:2021-08-06

micrObs – A customizable time-lapse camera for ecological studies - Winterl, Alexander; Richter, Sebastian; Houstin, Aymeric; Nesterova, Anna P.; Bonadonna, Francesco; Schneider, Werner; Fabry, Ben; Le Bohec, Céline; Paranhos Zitterbart, Daniel (HardwareX, 2020)
Camera traps for motion-triggered or continuous time-lapse recordings are readily available on the market. For demanding applications in ecology and environmental sciences, however, commercial systems often lack flexibility to freely adjust recording time intervals, suffer from mechanical component wear, and can be difficult to combine with auxiliary sensors such as GPS, weather stations, or light sensors. We present a robust time-lapse camera system that has been operating continuously since 2013 under the harsh climatic conditions of the Antarctic and Subantarctic regions. Thus far, we have recorded over one million images with individual cameras. The system consumes 122 mW of power in standby mode and captures up to 200,000 high-resolution (16 MPix) images without maintenance such as battery or image memory replacement. It offers time-lapse intervals between 2 s and 1 h, low-light or night-time power saving, and data logging capabilities for additional inputs such as GPS and weather data.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Automated camera system; Collective behavior; Ecology; Image processing; Remote sensing; Wildlife monitoring

Phase transitions in huddling emperor penguins - Richter, Sebastian; Gerum, Richard; Winterl, Alexander; Houstin, A.; Seifert, Maria; Peschel, J.; Fabry, Ben; Le Bohec, Celine; Paranhos Zitterbart, Daniel (Journal of Physics D: Applied Physics, 2018)
Emperor penguins (Aptenodytes forsteri) are highly adapted to the harsh conditions of the Antarctic winter: they are able to fast for up to 134 days during breeding. To conserve energy, emperor penguins form tight groups (huddles), which is key for their reproductive success. The effect of different meteorological factors on the huddling behaviour, however, is not well understood. Using time-lapse image recordings of an emperor penguin colony, we show that huddling can be described as a phase transition from a fluid to a solid state. We use the colony density as order parameter, and an apparent temperature that is perceived by the penguins as the thermodynamic variable. We approximate the apparent temperature as a linear combination of four meteorological parameters: ambient temperature, wind speed, global radiation and relative humidity. We find a wind chill factor of -2.9 °C (ms-1)-1, a humidity chill factor of -0.5 °C/%rel. humidity, and a solar radiation heating factor of 0.3 °C (Wm-2)-1. In the absence of wind, humidity and solar radiation, the phase transition temperature (50% huddling probability) is -48.2 °C for the investigated time period (May 2014). We propose that higher phase transition temperatures indicate a shrinking thermal insulation and thus can serve as a proxy for lower energy reserves of the colony, integrating pre-breeding foraging success at sea and energy expenditure at land due to environmental conditions. As current global change is predicted to have strong detrimental effects on emperor penguins within the next decades, our approach may thus contribute towards an urgently needed long-term monitoring system for assessing colony health.
CRIS-Team Scopus Importer:2022-08-05
Keywords: climate variability; collective behaviour; emperor penguin; environmental conditions; huddling; phase transition

Remote sensing of emperor penguin abundance and breeding success - Winterl, Alexander; Richter, Sebastian; Houstin, Aymeric; Barracho, Téo; Boureau, Matthieu; Cornec, Clément; Couet, Douglas; Cristofari, Robin; Eiselt, Claire; Fabry, Ben; Krellenstein, Adélie; Mark, Christoph; et al. (Nature Communications, 2024)
Emperor penguins (Aptenodytes forsteri) are under increasing environmental pressure. Monitoring colony size and population trends of this Antarctic seabird relies primarily on satellite imagery recorded near the end of the breeding season, when light conditions levels are sufficient to capture images, but colony occupancy is highly variable. To correct population estimates for this variability, we develop a phenological model that can predict the number of breeding pairs and fledging chicks, as well as key phenological events such as arrival, hatching and foraging times, from as few as six data points from a single season. The ability to extrapolate occupancy from sparse data makes the model particularly useful for monitoring remotely sensed animal colonies where ground-based population estimates are rare or unavailable.
CRIS-Team Scopus Importer:2024-06-14

RFIDeep: Unfolding the potential of deep learning for radio-frequency identification - Bardon, Gaël; Cristofari, Robin; Winterl, Alexander; Barracho, Téo; Benoiste, Marine; Ceresa, Claire; Chatelain, Nicolas; Courtecuisse, Julien; Fernandes, Flávia A.N.; Gauthier-Clerc, Michel; Gendner, Jean Paul; Handrich, Yves; et al. (Methods in Ecology and Evolution, 2023)
Automatic monitoring of wildlife is becoming a critical tool in the field of ecology. In particular, Radio-Frequency IDentification (RFID) is now a widespread technology to assess the phenology, breeding and survival of many species. While RFID produces massive datasets, no established fast and accurate methods are yet available for this type of data processing. Deep learning approaches have been used to overcome similar problems in other scientific fields and hence might hold the potential to overcome these analytical challenges and unlock the full potential of RFID studies. We present a deep learning workflow, coined “RFIDeep”, to derive ecological features, such as breeding status and outcome, from RFID mark-recapture data. To demonstrate the performance of RFIDeep with complex datasets, we used a long-term automatic monitoring of a long-lived seabird that breeds in densely packed colonies, hence with many daily entries and exits. To determine individual breeding status and phenology and for each breeding season, we first developed a one-dimensional convolution neural network (1D-CNN) architecture. Second, to account for variance in breeding phenology and technical limitations of field data acquisition, we built a new data augmentation step mimicking a shift in breeding dates and missing RFID detections, a common issue with RFIDs. Third, to identify the segments of the breeding activity used during classification, we also included a visualisation tool, which allows users to understand what is usually considered a “black box” step of deep learning. With these three steps, we achieved a high accuracy for all breeding parameters: breeding status accuracy = 96.3%; phenological accuracy = 86.9%; and breeding success accuracy = 97.3%. RFIDeep has unfolded the potential of artificial intelligence for tracking changes in animal populations, multiplying the benefit of automated mark-recapture monitoring of undisturbed wildlife populations. RFIDeep is an open source code to facilitate the use, adaptation, or enhancement of RFID data in a wide variety of species. In addition to a tremendous time saving for analysing these large datasets, our study shows the capacities of CNN models to autonomously detect ecologically meaningful patterns in data through visualisation techniques, which are seldom used in ecology.
CRIS-Team Scopus Importer:2023-11-10
Keywords: artificial intelligence; behaviour; machine learning; RFID; wildlife monitoring

Viscoelastic properties of suspended cells measured with shear flow deformation cytometry - Gerum, Richard; Mirzahossein, Elham; Eroles, Mar; Elsterer, Jennifer; Mainka, Astrid; Bauer, Andreas; Sonntag, Selina; Winterl, Alexander; Bartl, Johannes; Fischer, Lena; Abuhattum, Shada; Goswami, Ruchi; et al. (eLife, 2022)
Numerous cell functions are accompanied by phenotypic changes in viscoelastic prop-erties, and measuring them can help elucidate higher level cellular functions in health and disease. We present a high-throughput, simple and low-cost microfluidic method for quantitatively measuring the elastic (storage) and viscous (loss) modulus of individual cells. Cells are suspended in a high-viscosity fluid and are pumped with high pressure through a 5.8 cm long and 200 µm wide microflu-idic channel. The fluid shear stress induces large, ear ellipsoidal cell deformations. In addition, the flow profile in the channel causes the cells to rotate in a tank-treading manner. From the cell deformation and tank treading frequency, we extract the frequency-dependent viscoelastic cell properties based on a theoretical framework developed by R. Roscoe [1] that describes the deformation of a viscoelastic sphere in a viscous fluid under steady laminar flow. We confirm the accuracy of the method using atomic force microscopy-calibrated polyacrylamide beads and cells. Our measurements demonstrate that suspended cells exhibit power-law, soft glassy rheological behavior that is cell-cycle-dependent and mediated by the physical interplay between the actin filament and intermediate filament networks.
CRIS-Team Scopus Importer:2022-10-28